Sustainability Entrepreneurship Strategy in Increasing the Sustainability and Competitiveness of the Cocoa Industry - Sainab, Sainab; Kautsar, Muthia Natasya; Mardia, Mardia; Nahdah, Nahdah (Newinera Publisher, 2025)
The cocoa industry is undergoing complex market dynamics driven by increasing global awareness of sustainability issues. Sustainable entrepreneurship has emerged as a strategic approach to balancing economic performance, environmental protection, and social equity. This study aims to examine the key factors influencing the sustainability of the cocoa industry from a sustainable entrepreneurship perspective and to analyze its impact on economic, social, and environmental outcomes. A quantitative descriptive approach was employed, with data analyzed using Structural Equation Modeling (SEM). The results indicate that all measurement indicators exhibit outer loading values exceeding 0.70, confirming acceptable convergent validity. Sustainable entrepreneurship demonstrates a strong and statistically significant effect on the overall sustainability of the cocoa sector. Specifically, its application leads to enhanced business efficiency, improved social welfare, and greater adoption of environmentally responsible practices. Moreover, the high R² values for the sustainability constructs suggest that sustainable entrepreneurship serves as a major explanatory variable for performance across all three dimensions. These findings highlight the strategic role of sustainable entrepreneurship in fostering a resilient and sustainable cocoa industry. The implications provide valuable insights for policymakers, industry actors, and stakeholders in developing sustainability oriented cocoa agribusiness models.